2019
DOI: 10.1002/adfm.201809110
|View full text |Cite
|
Sign up to set email alerts
|

A Bioinspired Medical Adhesive Derived from Skin Secretion of Andrias davidianus for Wound Healing

Abstract: Existing surgical tissue adhesives on the market cannot meet the desired demand for clinical operations due to their limited adhesivity or undesired cytotoxicity. A new bioadhesive is derived from the skin secretion of Andrias davidianus (SSAD). This bioinspired SSAD has significantly stronger tissue adhesion than the fibrin glue and improved elasticity and biocompatibility when compared to the cyanoacrylate glue both ex vivo and in vivo. Additionally, the SSAD‐based adhesive decreases skin wound healing time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
118
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 139 publications
(121 citation statements)
references
References 61 publications
3
118
0
Order By: Relevance
“…No serious tissue toxicity or inflammation was observed in the surrounding skin tissue from the H&E staining (Figure 4c). We also examined the systemic toxicity of the PL‐Cat/Fe/ODex hydrogel [ 5 ] after eight weeks and the results showed that no toxicity was detected in the main organs (Figure 4d). The results indicate that the PL‐Cat/Fe/ODex hydrogel is safe when applied in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…No serious tissue toxicity or inflammation was observed in the surrounding skin tissue from the H&E staining (Figure 4c). We also examined the systemic toxicity of the PL‐Cat/Fe/ODex hydrogel [ 5 ] after eight weeks and the results showed that no toxicity was detected in the main organs (Figure 4d). The results indicate that the PL‐Cat/Fe/ODex hydrogel is safe when applied in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Full thickness skin incision [ 5 ] was used as wound model to test the wound closure performance of the PL‐Cat/Fe/ODex hydrogel. First, the ability to repeatedly close the incision was evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially, the adhesive dressing can avoid the secondary damage due to the fragility of soft tissue and localized stress and subsequent removal of non‐degradable sutures or staples, and simplify operation procedures, shorten recovery times, and improve patient care quality. [ 19 ] Catechol group contained substances have good biocompatibility and free radical scavenging ability, which can also show good tissue adhesiveness, self‐healing, and photothermal capacity after complexing with Fe 3+ . Combining the catechol–Fe 3+ coordination cross‐linked synthetic flexible polymer with UPy hydrogen bonding cross‐linked gelatin can prepare synthetic–natural hybrid physical double‐network hydrogel adhesive, integrating the flexible network of synthetic polymer, healing efficiency of natural gelatin, [ 1 ] antioxidant activity, photothermal sterilization, self‐healing and on demand photothermal removal.…”
Section: Introductionmentioning
confidence: 99%